Przebieg procesów prywatyzacji w Polsce (funkcjonalność i dysfunkcjonalność rozwiązań prawnych) - Marczuk, Stanisław (Wydział Prawa i Administracji UAM, 1995)
The term 'privatisation' has recently expanded to include not only the very fact of the change of ownership but also the social and political as well as economic conditions in which that change takes place.The paper lists factors and conditions conducive for effective privatisation. They include: 1) coexistence of political and economic reforms, 2) capability of the leaders of showing the society the benefits of privatisation, and provision of general economic education, 3) reduction of the resistance to privatisation which may be expressed by those groups of population which are threatened by privatisation (certain workers' groups/employees, certain government officers etc.), 4) principles of disclosure as well as social control and supervision of the sale of state owned enterprises, 5) avoiding situations where the public monopoly is being replaced with the private monopoly. In connection with the above, the economic and social effects of the privatisation of state owned enterprises in Poland are discussed. The conclusion is that changes in the privatisation policy are indispensable, requiring changes towards gaining more public support for the privatisation policy and improvement of the existing solutions.
Opportunities and threats affecting the privatisation processes in Poland